2015
DOI: 10.1101/gr.187039.114
|View full text |Cite
|
Sign up to set email alerts
|

Using genome-wide measures of coancestry to maintain diversity and fitness in endangered and domestic pig populations

Abstract: Conservation and breeding programs aim at maintaining the most diversity, thereby avoiding deleterious effects of inbreeding while maintaining enough variation from which traits of interest can be selected. Theoretically, the most diversity is maintained using optimal contributions based on many markers to calculate coancestries, but this can decrease fitness by maintaining linked deleterious variants. The heterogeneous patterns of coancestry displayed in pigs make them an excellent model to test these predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 57 publications
3
75
2
Order By: Relevance
“…In the current study, minimizing relationships based on matrix A had an unfavorable effect on the diversity at the genomic level compared to both genomic metrics SNPRM or ROHRM . This is in agreement with previous simulation studies that spanned multiple generations in the context of conservation [65, 66] and livestock breeding programs [19, 25, 27, 30, 67]. Based on simulations, Sonesson et al [25] found that the genomic rate of inbreeding was around 3 times higher when using optimal contributions constrained by pedigree versus genomic information.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, minimizing relationships based on matrix A had an unfavorable effect on the diversity at the genomic level compared to both genomic metrics SNPRM or ROHRM . This is in agreement with previous simulation studies that spanned multiple generations in the context of conservation [65, 66] and livestock breeding programs [19, 25, 27, 30, 67]. Based on simulations, Sonesson et al [25] found that the genomic rate of inbreeding was around 3 times higher when using optimal contributions constrained by pedigree versus genomic information.…”
Section: Discussionsupporting
confidence: 88%
“…4). Previous simulations, based on multiple generations showed that SNPRM maintains heterozygosity to a greater degree than ROHRM [66, 67], which is not surprising since the SNPRM is more closely related to the heterozygosity than the ROHRM . Within one generation, the level of heterozygosity was numerically the highest when the SNPRM was used for the majority of the quantiles across breeds compared to the ROHRM , which is in line with previous work, although the across-replicate standard deviation covered both means.…”
Section: Discussionmentioning
confidence: 92%
“…The best know strategy to achieve these goals is optimizing the contributions of the parents to minimize global coancestry in their offspring (Fernández et al, 2003). Recently, measures of coancestry based on IBD segments and on shared segments of the genome (Bosse et al, 2015) have been proposed as good balance between maintaining diversity and fitness, with a higher fitness than managing with molecular coancestry and higher diversity than managing with genealogical coancestry. Therefore, determining the occurrence of IBD segments in potential parents, thereby measuring their relatedness and coancestry, can be used to minimize the occurrence of long ROH in the offspring.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, according to Szpiech et al (2013), a significantly greater fraction of all genome-wide predicted damaging homozygotes falls in ROH, especially in long ROH, than would be expected from the corresponding fraction of non-damaging homozygotes in ROH. In livestock breeding and conservation, the power and potential benefit of this concept were recognised very soon by Bosse et al (2015), Zhang et al (2015b), and Nuijten et al (2016). We believe that this approach, when combined with estimation of inbreeding depression and some other innovative technologies such as gene editing (gene editing or genome editing is the insertion, deletion, or replacement of DNA at a specific site in the genome; Kim and Kim, 2014), might open the door to the management of detrimental load in genetically small populations.…”
Section: Future Opportunitiesmentioning
confidence: 99%